Inhibition of matrix metalloproteinase‐9 by a barbiturate‐nitrate hybrid ameliorates dextran sulphate sodium‐induced colitis: effect on inflammation‐related genes. (24th February 2017) - O'Sullivan, Shane; Wang, Jun; Pigott, Maria T; Docherty, Neil; Boyle, Noreen; Lis, Samuel Kana; Gilmer, John F; Medina, Carlos
Abstract : Background and Purpose: Matrix metalloproteinase‐9 (MMP‐9) is up‐regulated in ulcerative colitis and implicated in the pathology of the disease. In this study, we have examined the effects of a barbiturate‐based MMP inhibitor incorporating a nitric oxide donor/mimetic group (dinitrate‐barbiturate) on the intestinal injury induced by dextran sulphate sodium (DSS). Experimental Approach: In vivo experiments were carried out using male Wistar rats given 5% DSS ad libitum in drinking water. The dinitrate‐barbiturate, non‐nitrate equivalent, nitrate side chains alone or vehicle were administered rectally, twice daily. MMP‐9 release was measured by gelatin zymography, and analysis of gene expression was carried out using RT‐qPCR. TaqMan low density arrays were used to evaluate the expression of 91 inflammatory genes in the rat colon. Key Results: The dinitrate‐barbiturate inhibited the induction and activity of MMP‐9 during DSS colitis in the rat. This occurred in association with significant reductions in the colitic response to DSS as assessed by an established clinical disease activity index and a pathological colitis grade score. The compound modified expression rates of numerous inflammation‐related genes in the colon. Conclusions and Implications: This study demonstrated the efficacy of the dinitrate‐barbiturate in DSS‐induced colitis. Therefore, barbiturate‐nitrate hybrids may be developed as a promising anti‐inflammatory approach to the treatment of inflammatory bowel disease.